Frequency of fungi at different heights of Dongargarh, India - Sharma, K; Verma, J N (Current Botany, 2012)
Frequency of fungi at different height of Dongargarh was studied with the help of Petriplate method. Total 389 fungal colonies represented 31 fungal types from altitude and 18 fungal floras were isolated from ground level during the present investigation period. The fungal species were Cladosporium oxysporium, Fusarium Mycelia sterilia, Aspergillus, Penicillium, Curvularia, Cladosporium, Rhizopus,Trichoderma species were observed. Aspergillus niger observed as most frequent fungi from both side, altitude (83.33%) as well as ground level (75%). While minimum percentage frequency (8.33%) is observed for Neosartorya fischeri and A.terreus. on hill-top and A. oryzae, Dictyochlamydospora, Fusarium pallidoroseum at ground level.